Study of hydroxyapatite based on Aceh's bovine bone coating on 314L stainless steel as a candidate for coating dental implant materials - Irhamni IRHAMNI; Ireka SALSABILA; Fauzi FAUZI; Zulfalina ZULFALINA; Zulkarnain JALIL (Dentistry Faculty, 2021)
ABSTRACT The use of hydroxyapatite (HAp) based on Aceh's bovine bone has been studied as a candidate for thecoating dental implant materials. In this study, the effect of sintering temperature and viscosity on the thickness ofthe hydroxyapatite layer on the 316L stainless steel plaque was observed. The hydroxyapatite was synthesized frombovine bone and then coated on the plate using the dip-coating method. Then, the plate surface was dried at 110 Cfor 30 minutes and sintered with various temperatures of 500, 600, 700, and 800 C for 1 hour. The plate that hasbeen coated with hydroxyapatite was characterized using a thickness meter to measure the thicknesses of the layer.The water composition of 10 grams/L had a better effect on the thickness of the implant material coated with HApbeef bone compared to the water composition of 4, 6, and 8 (gram/L) (p0.05). On the other hand, the temperaturefactor did not affect changes in the thickness of the implant material (p0.05). The higher water composition (10grams/L) resulted in a decrease in the thickness of the implant material coated with beef bone HAp. KEYWORDS: Hydroxyapatite, sintering temperature, viscosity, dip-coating, thickness, coating dental implant